Virtual reality and embodiment: rethinking self-construction and identity in therapeutic contexts - Vasudha, Vasudha; Choudhary, Shalini (Frontiers in Virtual Reality, 2026)
Immersive virtual reality has surfaced as a revolutionary instrument in psychology, clinical practice, and neuroscience creating unique opportunities to explore embodiment, identity, and therapeutic applications. This review advances the field by reframing embodiment as a core psychological mechanism linking perception, identity, and therapeutic change in immersive virtual reality. Embodiment in VR functions as a psychological process through which perceptual, emotional, and identity-level changes emerge. These processes have demonstrated relevance to clinical practice, including pain management, cognitive rehabilitation, and interventions for anxiety, depression, and social phobia. This mini review synthesizes current research across these domains, highlighting the mechanisms through which VR shapes self-perception and psychological functioning. By integrating findings from empirical studies and theoretical frameworks, the review identifies both opportunities and limitations in VR research and practice, providing a foundation for future investigations into its potential to enhance wellbeing and support personal transformation. By reframing embodiment as an active process rather than a perceptual illusion, this review clarifies how immersive VR can produce both immediate experiential effects and long-term changes in self-perception and therapeutic outcomes. However, it also highlights that current research has gaps in theoretical clarity and methodology, emphasizing the need for more personalized, accessible, empirical and long-term studies in the future.